2009
DOI: 10.1002/hed.21123
|View full text |Cite
|
Sign up to set email alerts
|

Initial clinical experience with helical tomotherapy for head and neck cancer

Abstract: HT appears to achieve clinical outcomes comparable to contemporary series reporting on IMRT for head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…4). This is consistent with other studies on the recurrence sites of head and neck tumors in association with the isodoses on the planning CT (14). Thus, lateral positioning with daily-corrected setup errors did not jeopardize the accurate delivery of the dose to the target volume.…”
Section: Discussionsupporting
confidence: 93%
“…4). This is consistent with other studies on the recurrence sites of head and neck tumors in association with the isodoses on the planning CT (14). Thus, lateral positioning with daily-corrected setup errors did not jeopardize the accurate delivery of the dose to the target volume.…”
Section: Discussionsupporting
confidence: 93%
“…Preliminary results are comparable with those obtained with segmental MLC-based IMRT in terms of tumour control with a locoregional control and an overall survival of 75-80% and 66-82%, respectively, at 2 years [8][9][10][11][12]. Only one published clinical study showed the ability of TOMO to spare the parotid gland and preserve the salivary function [44].…”
Section: Helical Tomotherapysupporting
confidence: 75%
“…12 Volumetricmodulated arc therapy, a form of rotational IMRT, and stereotactic RT, a form of highly focused irradiation using tridimensional tumor targeting, also offer advantages. 13 Arc therapy reduces IMRT delivery time from 20 minutes to fewer than 5 minutes, while optimizing dose homogeneity and normal tissue sparing, [14][15][16][17][18][19][20][21][22][23][24][25] including parotid gland sparing. 26 Stereotactic fractionated RT allows for the generation of x-ray beams from a single electronic source, which can be rotated or moved around a central focus.…”
Section: Chemoradiation Therapymentioning
confidence: 99%